Recent Advances in CNS P2X7 Physiology and Pharmacology: Focus on Neuropsychiatric Disorders - Bhattacharya, Anindya (Frontiers in Pharmacology, 2018)
The ATP-gated P2X7 ion channel is an abundant microglial protein in the CNS that plays an important pathological role in executing ATP-driven danger signal transduction. Emerging data has generated scientific interest and excitement around targeting the P2X7 ion channel as a potential drug target for CNS disorders. Over the past years, a wealth of data has been published on CNS P2X7 biology, in particular the role of P2X7 in microglial cells, and in vivo effects of brain-penetrant P2X7 antagonists. Likewise, significant progress has been made around the medicinal chemistry of CNS P2X7 ligands, as antagonists for in vivo target validation in models of CNS diseases, to identification of two clinical compounds (JNJ-54175446 and JNJ-55308942) and finally, discovery of P2X7 PET ligands. This review is an attempt to bring together the current understanding of P2X7 in the CNS with a focus on P2X7 as a drug target in neuropsychiatric disorders.